The Analysis of the Notary Regional Supervisory Board on the Storage of Notary Protocols that are more than Twenty-Five Years - Evita Rizkiana (Jurnal Daulat Hukum, 2022)
The notary makes authentic deeds regarding all the deeds, agreements,  and conditions required by laws and regulations and/or are desired by interested parties to be included in an authentic deed, guarantees certainty that coincides with the making of the deed, saves the deed, distributes grosse, deposits and quotes the deed , all of that during the making of the deed was also not delegated or excluded to other officials or other people determined by law ". A message made by or in the presence of a universal official in power is said to be an authentic deed, by providing enough evidence for both parties and their heirs and all those who have the right to override all the things mentioned in the message and also about what is stated in the message. The message is only a notification, but what was later notified was directly related to the subject matter of the deed. An authentic deed has formal, material and binding strength. The profession of a notary among residents because residents need their services after that socializes them to residents.